Investigation of cause-specific mortality rates of European Union member and candidate countries by World Health Organization global health estimate categories - Sığırlı, Deniz; Kılıçarslan, Sultan (The European Research Journal, 2022)
Objectives: It is aimed to examine the position of our country and the European Union member and candidate countries in terms of mortality rates according to the motality causes defined in global health estimate categories determined by the World Health Organization and to reveal the similarities or differences. Methods: According to the World Health Organization global health estimate categories given in the Global Burden of Disease 2019 study of World Health Organization, age-standardized mortality rates per 100,000 population were obtained for a total of 31 European Union member and candidate countries, and the muldimensional scaling analysis performed groups of the countries according to their dimensions obtained from multidimensional scale were determined and among these groups comparisons have been made. Results: As a result of applying multidimensional scaling analysis, it was seen that countries can be represented in two-dimensional space according to the variables of interest. Conclusions: It has been observed that our country differs from countries with cardiovascular diseases in the first dimension from the World Health Organization categories, while in the second dimension, infectious and parasitic diseases differ from countries with high standardized mortality rates.